Spontaneously hypertensive rat vascular smooth muscle cells in culture exhibit increased growth and Na+/H+ exchange. - Berk, B C (1989)
The cellular mechanisms responsible for abnormalities in spontaneously hypertensive rat (SHR) vascular smooth muscle cell (VSMC) growth and vasoreactivity are not defined. Because Na+/H+ exchange, which we have previously demonstrated in cultured VSMC, plays an essential role in mediating growth factor responses, we hypothesized that abnormalities in SHR growth regulation might be reflected in the activity of this transporter. To test this hypothesis, we studied DNA synthesis and Na+/H+ exchange (measured as the rate of amiloride-sensitive intracellular alkalinization or Na+ influx) in early subcultures (less than 6) of aortic VSMC from 12-wk-old SHR and Wistar Kyoto (WKY) animals. Serum-deprived SHR VSMC grew more rapidly in response to 10% serum with an increase in [3H]thymidine incorporation of 439% compared with 191% in WKY controls. Basal intracellular pH (pHi) values determined by fluorescent pH measurements were 7.37 +/- 0.04 and 7.27 +/- 0.03 (P less than 0.05) in early passage SHR and WKY, respectively. Acid recovery (initial pHi = 6.8) by SHR VSMC was faster than by WKY VSMC as measured by alkalinization (1.8 +/- 0.6 vs. 0.8 +/- 0.2 mmol H+/liter.min, P less than 0.05) or by amiloride-sensitive 22Na+ influx (14.5 +/- 1.2 vs. 4.0 +/- 0.5 nmol Na+/mg protein.min, P less than 0.05). In comparison to WKY cells early passage SHR VSMC exhibited 2.5-fold greater alkalinization and amiloride-sensitive 22Na+ influx in response to 100 nM angiotensin II. During serial passage, WKY cells acquired enhanced Na+/H+ exchange and growth rates so that by passage 6, these differences were no longer present. These findings in early cultures of SHR VSMC, removed from the in vivo neurohumoral milieu, suggest that increased Na+/H+ exchange in SHR may reflect alterations in Na+ homeostasis that might contribute to altered SHR VSMC function such as enhanced growth and vasoreactivity.